Rice Straw In Vitro Digestibiliy of Combination Treatments Alkali, fermented with Cellulolytic, Lignolytic and Lactic Acid Microbes with Suplementation of Sulfur - . Harfiah; M. Z. Mide (Jurnal Ilmu dan Teknologi Peternakan, 2014)
The purpose of research was to improve digestibility of rice straw for ruminant feeding. To attain the aim, three steps of experiment have been conducted. The first step was the isolation of lactic acid bacterial (Lactobacillus sp) and cellulolytic bacterial (Acetobacter liqufacens) from the ruminal fluid of cattle and lignolytic microbes (white rot fungi) from palm oil waste and proliferated at compos media. The second step was to test the inoculum of lactic acid, cellulolytic, and lignolytic bacteria in breaking down fibre fraction of the rice straw. Those microbes were fermented with alkaline treated rice straw and sulphuric + molasses. The experiment was carried out factorially (3 x 5) according to completely randomised design. Factor A was the fermentation time, i.e. 10, 20, and 30 days. Factor B was the fermentation types, which were B1=alkaline treated rice straw+urea, B2=B1+lactic acid bacterial, B3=B2+cellulolytic bacterial, B4=B3+white rot fungi, and B5=B4+sulphuric and molasses. The third period was in vitro evaluation of the fermented rice straw. Parameters measured were in vitro dry matter and organic matter digestibility. Analysis of variance showed that the length of fermentation and their interaction with types of fermentation had no significant effect on in vitro dry matter and organic matter digestibility of fermented rice straw but fermentation types affected (p<0,05) in vitro dry matter and organic matter digestibility of rice Straw. It is concluded from this experiment that fermentation of alkaline treated rice straw with cellulolytic bacteria, white rot fungi, and lactic acid microbes with the addition of molasses and sulfur can increase in vitro digestibility of rice sraw.